2004
DOI: 10.1097/00005176-200403000-00015
|View full text |Cite
|
Sign up to set email alerts
|

Constipation and Intestinal Neuronal Dysplasia Type B: A Clinical Follow-up Study

Abstract: In young patients, constipation related to IND B can be treated successfully by conservative treatment regimens, including diet, laxatives, and prokinetic drugs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 26 publications
0
13
0
Order By: Relevance
“…This wide variation may be attributable to the lack of consensus on the diagnostic criteria [6,31] . There is also an irregular geographical distribution; the highest rates of diagnosis are in Euro pean countries, which can be explained by the fact that the majority of the published research comes from this continent [32] . The latest published series by Taguchi et al [33] (2014) involved a retrospective multicenter study of cases of INDB in 167 centers in Japan from 2000 to 2009.…”
Section: Epidemiologymentioning
confidence: 99%
See 4 more Smart Citations
“…This wide variation may be attributable to the lack of consensus on the diagnostic criteria [6,31] . There is also an irregular geographical distribution; the highest rates of diagnosis are in Euro pean countries, which can be explained by the fact that the majority of the published research comes from this continent [32] . The latest published series by Taguchi et al [33] (2014) involved a retrospective multicenter study of cases of INDB in 167 centers in Japan from 2000 to 2009.…”
Section: Epidemiologymentioning
confidence: 99%
“…Patients with IND have been subjected to different treatments moda lities, that may vary from clinical management, to surgical procedures [57] . Clinical management includes dietary changes, laxatives and enemas [6,32] . Schimpl et al [32] (2004) reported satisfactory results in 80% of 105 patients treated with dietary changes, cisapride, laxatives and enemas, in a median follow up period of 7.2 years.…”
Section: Treatmentmentioning
confidence: 99%
See 3 more Smart Citations